Lupinus lanatus Benth, Lupinus guaraniticus (Hassl.) C. P. Sm., Lupinus paranensis C. P. Sm. (Fabaceae) e Waltheria douradinha Saint Hilaire (Sterculiaceae): isolamento e identificação de seus metabólitos e atividade biológica - Tiburski Neto, Alexandre (2015)
The part of our constant search for new bioactive secondary metabolites of plant origin, the aerial parts of three species of the genus Lupinus (Leguminoseae), and the bark of the roots of the species Waltheria douradinha Sain Hilaire (Sterculiaceae), were submitted to phytochemical investigation. In this research, they were isolated and identified 14 compounds, which was exposid several biological activities. Among the activities performed, the compounds were evaluated against antimicrobial, antioxidant enzyme (POP and DPPIV) and also bacteriolityc activity. Two of the isolated compounds, (+)Lanatina A (L. paranensis) and Antidesmona (W. douradinha) shawed bacteriolityc activity. The test showed that these compounds have bacteriolityc activity, especially against Gram-negative. The Antidesmona presented better lytic potential in the concentration of 12.5 μg/mL against the microorganism Salmonella typhimurium ATCC 14028. For this bacterium, Antidesmona alkaloid produced a cell wall lysis of approximately 30% between 4-6 hours (P <0.0001). The alkaloid extracts W. douradinha, collected in four different regions of Rio Grande do Sul - Brazil, was analyzing its chemical composition by HPLC. Analysis of the chemical composition of the basic extracts was compared with soil analyzes the place collection of plant. These results revealed significant differences in the chemical compositions of alkaloid extracts of Waltheria douradinha Sain Hilaire and were important guides of new collection sites these species.